Demolition site at Pemberton Square, ca. 1896 - J. W. Black & Co. (Tufts Archival Research Center, 2005)
Demolition site located at Pemberton Square. Houses are included in the photograph. 7 3/4 x 4 3/8, 8 1/2 x 5 1/4 overall Cabinet photographs